The Impact of Marketing Strategy and Facilities on the Decision to Become a Murabahah Financing Customer - Masithoh, Fitria Nur; Mahmud, Mahmud; Muhammad Ain Raafi’ud Darajaat (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine: 1) the influence of marketing strategy on the decision to become a murabahah financing customer at BPRS Lantabur Mojokerto Branch. 2) The impact of marketing facilities on the decision to become a murabahah financing customer at BPRS Lantabur Mojokerto Branch. 3) the impact of marketing strategy and facilities simultaneously on the decision to become a murabahah financing customer at BPRS Lantabur Mojokerto Branch. Based on the results of data analysis, the Marketing Strategy variable is known to have a partially significant influence on the Decision to Become a Murabahah Financing Customer at BPRS Lantabur Mojokerto Branch, this is based on the value of tcount > ttable or 4,062 > 1,999 with a significance value smaller than 0.05 (0.000). The Facilities variable partially has a significant impact on the Decision to Become a Murabahah Financing Customer at BPRS Lantabur Mojokerto Branch, this is based on the value tcount > ttable or 13,712 > 1,999 with a significant value smaller than 0.05 (0.000).